(untitled) (The Pakistan Development Review, 2020)
Volatility in discretionary public spending has diverse implications for the overall economic performance of economies. In this study, we examine the impact of volatile nonsystematic discretionary public spending on economic growth. By employing cross-country data of 74 developed and developing economies, we find that volatility in non-systematic discretionary public spending has an adverse impact on economic growth. In particular, such impact is severe in the case of less developed economies. Our findings are robust to the problem of endogeneity. In order to ensure the accuracy of the results, we conduct sufficient sensitivity analysis by incorporating a bunch of potential control variables. In most of the cases, the results with regard to the policy volatility remain intact. This suggests that effective spending rules, i.e. permanent numerical limits, should be imposed on budgetary aggregates to restrain governments from the volatile use of discretionary spending. JEL Classification: H3; H5 Keywords: Volatility in Discretionary Public Spending, Economic Growth, Effective Spending Rule